PENGARUH HUMAN RELATION, LINGKUNGAN KERJA, PELATIHAN DAN PENGEMBANGAN SDI TERHADAP ETOS KERJA PEGAWAI BANK SYARIAH - Suryani, Frischa Dwi; Aji, Tony Seno (Universitas Negeri Surabaya, 2020)
The study inteds to measure and recognize the influence of Human Relation, the physical condition of the work environment, job training, employee development on work ethic at the bank Syariah Bukopin branch office in Surabaya. The population and sample all employee totaling 50 people. The results of the analysis showed that Human Relation had no influence on work ethic in Bukopin Syariah Bank branch office Surabaya, while physical condition of the work environment, on the job training, employee development has a positive influence on employee the work ethic in Bukopin Syariah Bank branch office Surabaya. While the results of R2 of 67.4% means the variable has a big contribute to work ethic.